Monetary policy and the gender pay gap: evidence from UK households. Issue 21 (15th December 2019) - Apergis, Nicholas; Hayat, Tasawar; Kadasah, Nasser A.
ABSTRACT: This paper studies how monetary policy decisions affect the gender pay gap across UK households through a survey database. The results signify the impact of monetary policy shocks on the gap; monetary authorities' decisions carry welfare effects for households through their pay income.